Genetic deletion of Urocortin 3 does not prevent functional maturation of beta cells. Issue 1 (July 2020) - Huang, Jessica L; Lee, Sharon; Hoek, Pelle; van der Meulen, Talitha; Van, Richard; Huising, Mark O
Abstract : There is great interest in generating functionally mature beta cells from stem cells, as loss of functional beta cell mass contributes to the pathophysiology of diabetes. Identifying markers of beta cell maturity is therefore very helpful for distinguishing stem cells that have been successfully differentiated into fully mature beta cells from stem cells that did not. Urocortin 3 (UCN3) is a peptide hormone whose expression is associated with the acquisition of functional maturity in beta cells. The onset of its expression occurs after other beta cell maturity markers are already expressed and its loss marks the beginning of beta cell dedifferentiation. Its expression pattern is therefore tightly correlated with beta cell maturity. While this makes UCN3 an excellent marker of beta cell maturity, it is not established whether UCN3 is required for beta cell maturation. Here, we compared gene expression and function of beta cells from Ucn3 -null mice relative to WT mice to determine whether beta cells are functionally mature in the absence of UCN3. Our results show that genetic deletion of Ucn3 does not cause a loss of beta cell maturity or an increase in beta cell dedifferentiation. Furthermore, virgin beta cells, first identified as insulin-expressing, UCN3-negative beta cells, can still be detected at the islet periphery in Ucn3 -null mice. Beta cells from Ucn3 -null mice also exhibit normal calcium response when exposed to high glucose. Collectively, these observations indicate that UCN3 is an excellent mature beta cell marker that is nevertheless not necessary for beta cell maturation.